Severe sex differentiation disorder in a boy with a 3.8 Mb 10q25.3–q26.12 microdeletion encompassing EMX2. Issue 10 (26th June 2014) - Piard, Juliette; Mignot, Brigitte; Arbez‐Gindre, Francine; Aubert, Didier; Morel, Yves; Roze, Virginie; McElreavey, Kenneth; Jonveaux, Philippe; Valduga, Mylène; Van Maldergem, Lionel
Abstract : The molecular basis of male disorders of sex development (DSD) remains unexplained in a large number of cases. EMX2 has been proposed to play a role in the masculinization process for the past two decades, but formal evidence for this causal role is scarce. The aim of this study is to yield additional support to this hypothesis by reporting on a male patient who presented with 46, XY DSD, a single kidney, intellectual disability, and the smallest microdeletion including EMX2 reported to date. EMX2 haploinsufficiency is likely to explain the masculinization defect observed in our patient, similar to what has been described in the mouse. In the case of cytogenetically diagnosed cases, deletions of EMX2 have been associated with a wide range of DSD, ranging from hypospadias to complete sex reversal. © 2014 Wiley Periodicals, Inc.